2013
DOI: 10.1590/s1984-70332013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of resistance genes to races 1, 3 and 5 of Podosphaera xanthii in melon PI 414723

Abstract: -The fungus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
1
6
0
2
Order By: Relevance
“…On the other hand, genotypes with genes or QTL located in LG II or XII seem to have a resistance type II. The melon line “PI 414723”, with a resistance gene located in LG II controlling at least resistance to races 1, 2, 3, and 5 [ 33 , 35 , 42 ], showed a resistance type II according to our results, as well as it is described by Kuzuya et al [ 20 ]. This same resistance was noticed in RIL88 and RIL276, both resistant to powdery mildew due to the presence of a possible recessive gene in LG XII coming from “TGR-1551” [ 43 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, genotypes with genes or QTL located in LG II or XII seem to have a resistance type II. The melon line “PI 414723”, with a resistance gene located in LG II controlling at least resistance to races 1, 2, 3, and 5 [ 33 , 35 , 42 ], showed a resistance type II according to our results, as well as it is described by Kuzuya et al [ 20 ]. This same resistance was noticed in RIL88 and RIL276, both resistant to powdery mildew due to the presence of a possible recessive gene in LG XII coming from “TGR-1551” [ 43 ].…”
Section: Discussionsupporting
confidence: 87%
“…From both parental melon accessions, three lines were selected by phenotypic and molecular analyses from previous studies: the RIL88 and RIL276, two recombinant inbred lines obtained after seven self-crossings from the cross” TGR-1551” × “Bola de Oro”, both also resistant to races 1, 2 and 5, due possibly to the presence of a recessive gene from “TGR-1551” [ 43 ]; and the NIL21, a near-isogenic line obtained after five backcrossing from the same cross “TGR-1551” × “Bola de Oro” and resistant to races 1, 2, and 5 possibly due to the dominant gene related to the QTL Pm-R [ 36 ]. Moreover, several melon accessions with differential response to powdery mildew races were used: “PMR 45”, resistant to race 1 and carrying the dominant gene Pm-1 or Pm-A [ 34 , 45 ], “WMR 29”, resistant to races 1, 2, and 3 and carrying one dominant gene Pm-w or Pm-B [ 33 , 34 ], and “PI 414723”, resistant to races 1, 2, 3, and 5 and conferred by different genes according to various authors [ 33 , 35 , 42 , 46 ]. The experiments with all these melon lines were carried out in two locations, and plants were grown in two different environments: at 22 °C, 70% RH, 16/8 h light/dark in a growth chamber in the department of Phytopathology at the Technische Universität München (TUM), in Germany, and at 18–22 °C and 25–30 °C in a climatic chamber at the Experimental Station of the IHSM “La Mayora” (CSIC-UMA) in Malaga, Spain.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the genetic map built in this study, no changes in the chromosome assignment have been observed and the relative order of the markers is also maintained in almost all cases when compared to SNP maps recently developed (Diaz et al 2014;Perpiñá et al 2016) and with the melon consensus map (Diaz et al 2011;Diaz et al 2015). The marker density and the gap length are on the order of those maps described in melon with a similar number of markers (Fazza et al 2013) but, as expected, they are lower in terms of marker density than those reported in highly saturated maps (Deleu et al 2009;Diaz et al 2011).…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, the identification of genotypes resistant to race 1 of P. xanthii is an important contribution to improvements in melon farming. However, considering the frequency of resistant inbred lines obtained from crossings, it can be deduced that the genetic control of resistance to this pathogen is not a simple task, as evidenced by Fazza et al (2013). Further studies should be carried out for most consistent results, as a specific inheritance.…”
Section: Resultsmentioning
confidence: 99%